PERANCANGAN IKLAN LAYANAN MASYARAKAT PEMBUATAN MEDIA TANAM DENGAN MEMANFAATKAN BARANG-BARANG BEKAS - Suprianingsih Suprianingsih; Desipriani Desipriani (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
Public service advertisement is an extension or socialization made to provide information or education to the public about something that is beneficial to the community, both financially and non-financially. Planting media is a container or place to grow plants, both flowers, fruits and vegetables. Used goods are items that are no longer used, such as drink bottles, broken buckets and others, used goods are often considered as household waste that will be just thrown away. This public service advertisement is designed to educate the public to be able or willing to manage household waste produced into new goods that have artistic value and selling value.